Application of direct virtual coil to dynamic contrast‐enhanced MRI and MR angiography with data‐driven parallel imaging. Issue 2 (25th February 2013) - Wang, Kang; Beatty, Philip J.; Nagle, Scott K.; Reeder, Scott B.; Holmes, James H.; Rahimi, Mahdi S.; Bell, Laura C.; Korosec, Frank R.; Brittain, Jean H.
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the feasibility of direct virtual coil (DVC) in the setting of 4D dynamic imaging used in multiple clinical applications. Theory and Methods Three dynamic imaging applications were chosen: pulmonary perfusion, liver perfusion, and peripheral MR angiography (MRA), with 18, 11, and 10 subjects, respectively. After view‐sharing, the k‐space data were reconstructed twice: once with channel‐by‐channel (CBC) followed by sum‐of‐squares coil combination and once with DVC. Images reconstructed using CBC and DVC were compared and scored based on overall image quality by two experienced radiologists using a five‐point scale. Results The CBC and DVC showed similar image quality in image domain. Time course measurements also showed good agreement in the temporal domain. CBC and DVC images were scored as equivalent for all pulmonary perfusion cases, all liver perfusion cases, and four of the 10 peripheral MRA cases. For the remaining six peripheral MRA cases, DVC were scored as slightly better (not clinically significant) than the CBC images by Radiologist A and as equivalent by Radiologist B. Conclusion For dynamic contrast‐enhanced MR applications, it is clinically feasible to reduce image reconstruction time while maintaining image quality and time course measurement using the DVC technique. Magn Reson Med 71:783–789, 2014. © 2013 Wiley Periodicals, Inc.